The Numismatic Evidence on the Roman Harbour of Patrai - Papageorgiadou, Charikleia (Tekmeria, 2015)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Patrai, where Augustus founded a roman colony held a favorable position for the control not only of the northern Peloponnesian coastline but also the routes in the Aetolia and Locris. Although a maritime trade station, the references to its harbour is very scanty, while its ancient remains are almost totally destroyed by the modern city’s expansion. However, the installations of an important harbour can be attested in the numismatic evidence, offered by two issues dated to the reign of Commodus and Geta, which coincide with the archaeological one supporting the idea of a project to restore, enlarge or reconstruct the port during the reign of Commodus. This is perhaps the cause for the more realistic and more detailed rendering of the monuments depicted. The issues struck under Geta, in a more elliptic artistic rendering, might have been commemorative, to honour his predecessor’s benefaction to the colony. It is worth noticing that some of the buildings and statues which are shown can be identified to similar types depicted on other issues of the city, not only dated to the reigns of Commodus and Geta, but to other periods as well . Few Greek cities depict their harbours on their coins, most of them located in the region of the Peloponnese and dated to the Antonine and the Severi period. Their harbours underwent extensive reconstructions during Roman times and were transformed into major centres in the naval and commercial network of the period. In fact, it seems that the flourishing of a net of cities in the northern Peloponnesian coast as commercial centres was the trigger for the issuing of these coins promoting their predominance in the sea routes and commemorating actual construction works in their ports. The scarcity of the coins depicting harbours and the limited numbersofissues could confirm that these pieces were meant to celebrate or commemorate a construction program referring to the city’s port under the auspices of the emperor and his representatives. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>